TEORI VYGOTSKY DAN IMPLIKASINYA TERHADAP PEMBELAJARAN MATEMATIKA - Santoso Yohanes, Rudi (Widya Warta, 2010)
Vygotsky was born in Orsha, Russia, 1896 and died in Moskow, 1934 due to tuberculosis he had suffered since the age of 38. In his so short but very productive lifetime, he produced a lot of psychology theories about intellectual development. The theories are, among others, concerned with the role of social interaction in cognitive development, the dialectic of mind and language, concept development, and the zone of proximal development. This article discusses only two of those theories namely, the role of social interaction and the zone of proximal development, as well as their implications in mathematics learning.